Reduction-induced facile isomerisation of metallacarboranes: synthesis and crystallographic characterisation of 4-Cp-4, 1, 2-closo-CoC2B9H1112. Issue 35 (21st September 2015) - Man, Wing Y.; Rosair, Georgina M.; Welch, Alan J.
<x xml:space="preserve">Abstract</x> One-electron reduction of 3-Cp-3, 1, 2-closo-CoC2B9H11 followed by heating to reflux in DME (b.p. 85 °C) induces isomerisation to 4-Cp-4, 1, 2-closo-CoC2B9H11.